ICU related neuromuscular complications - Digala, Lakshmi; Govindarajan, Raghav (RRNMF Neuromuscular Journal, 2020)
The spectrum of neuromuscular diseases encountered in the ICUs today has rapidly evolved over the last decades. Multiple predisposing factors are involved in the development of neuromuscular complications in intensive care patients. Those complications broadly classified into weakness from the preexisting neuromuscular disease exacerbated by critical illness or the complication of the critical illness itself. Patients, when unresponsive, confused, or sedated precludes careful clinical examination. A careful schematic approach that involves acquiring extensive history, any underlying infections, use of any offending medications, and the course of presenting illness will help in delineating the underlying etiology. Here in this review, we describe many causes and the pathophysiology that contribute to the development of neuromuscular weakness in the ICU. A comprehensive investigation protocol must strictly be adhered to all the cases in the ICU settings to reduce the mortality and morbidity.